Atividade antimicrobiana de actinobactérias endofíticas de Sorghum s.p. contra microrganismos de interesse clínico - ALMEIDA NETO, Geraldo Walter de (Universidade Federal do Oeste do Pará, 2024)
Endophytic actinobacteria make up a broad and diverse range of Gram-positive, filamentous bacteria, which are distinguished by the production of secondary metabolites with ample antimicrobial activity. Considering the applications in the pharmaceutical industry the present study aims to select endophytic actinobacteria from Sorghum sp. (sorghum) with potential antimicrobial action against microorganisms of clinical interest. The study was based on descriptive, experimental and quantitative-qualitative analysis. 41 actinobacteria from the Microbiology Laboratory Laboratory of the Federal University of Pará were analyzed and reactivated by culture in International Streptomyces Project 2 - ISP2 medium for 7 days at 30°C for the development of the aerial mycelium on the entire surface of the culture medium. The evaluation of the antimicrobial activity of actinobacteria was performed by the Gelose Block technique, transferring circular blocks containing the colonies of actinobacteria to the culture medium previously inoculated with the test microorganisms Staphylococcus aureus, Candida krusei, Pseudomonas aeruginosa and Escherichia coli. After incubation for 48 h at 30°C (yeast) and 24 h at 37°C (bacteria), the growth inhibition halos around the blocks were recorded. The Matsuura (2004) scale was used to determine the intensity of the antimicrobial activity. Of the 41 endophytic actinobacteria evaluated, 17(41.4%) were active against at least one of the pathogenic microorganisms tested. A total of 4(9.8%) presented antimicrobial activity against a single pathogen, while 14(36.8%) presented antimicrobial activity against two or three pathogens, being Staphylococcus aureus, Candida krusei and Pseudomonas aeruginosa. No endophytic actinobacteria from Sorghum sp. was active against E. coli. The mean inhibition halos varied between 8.8 and 22 mm, with the highest inhibition halos being found against P. aeruginosa, with inhibition halos between 11 and 22 mm of diameter and against C. krusei with inhibition halos between 9 and 19mm. The actinobacteria that presented the highest degree of antimicrobial activity were SIL 4B (21.6mm), SIL 8A (21.3mm), against P. aeruginosa and SIL 27 (19mm) SIL 40 (16mm) against C.krusei. In view of the data obtained, we verified the potential of the Amazon biome, an environment little known for its microbiota, which holds bioactive substances with promising antimicrobial activity. The results confirm that endophytic actinobacteria of the genus Streptomyces sp. of Sorghum sp. are presented as a potential source in the production of antimicrobial substances against Gram-negative bacteria and yeast fungi.